Efisiensi Pangan di Kabupaten dan Kota Blitar Dalam Perspektif Ekonomi Islam - Jeka Widiatmanta (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research analyzes the consumption behavior patterns of the people of Blitar Regency and City in the context of national food efficiency from an Islamic economic perspective. The aim of the research is to identify people's consumption behavior patterns, the food efficiency strategies implemented, and the obstacles faced in national food efficiency efforts. The research method used is a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observation and documentation. The research results show that the consumption patterns of Blitar people tend to shift from staple food to non-food as prosperity increases. Food efficiency efforts are carried out through increasing production at low costs and optimizing income. However, there are obstacles in the form of uneven efficiency in the production to consumption chain. This study recommends increasing public awareness to avoid wasting the implementation and concept of maslahah in consumption patterns according to Islamic teachings.